Catalysis : an integrated approach to homogeneous, heterogeneous and industrial catalysis - Moulijn, Jacob A.; Leeuwen, P. W. N. M. van (Piet W. N. M.); Santen, R. A. van (Rutger A.); ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 1993)
Catalysis is a multidisciplinary activity which is reflected in this book. The editors have chosen a novel combination of basic disciplines - homogeneous catalysis by metal complexes is treated jointly with heterogeneous catalysis with metallic and non-metallic solids. The main theme of the book is the molecular approach to industrial catalysis. In the introductory section Chapter 1 presents a brief survey of the history of industrial heterogeneous and homogeneous catalysis. Subsequently, a selection of current industrial catalytic processes is described (Chapter 2). A broad spectrum of important catalytic applications is presented, including the basic chemistry, some engineering aspects, feedstock sources and product utilisation. In Chapter 3, kinetic principles are treated. The section on fundamental catalysis begins with a description of the bonding in complexes and to surfaces (Chapter 4). The elementary steps on complexes and surfaces are described. The chapter on heterogeneous catalysis (5) deals with the mechanistic aspects of three groups of important reactions: syn-gas conversion, hydrogenation, and oxidation. The main principles of metal and metal oxide catalysis are presented. Likewise, the chapter on homogeneous catalysis (6) concentrates on three reactions representing examples from three areas: carbonylation, polymerization, and asymmetric catalysis. Identification by in situ techniques has been included. Many constraints to the industrial use of a catalyst have a macroscopic origin. In applied catalysis it is shown how catalytic reaction engineering deals with such macroscopic considerations in heterogeneous as well as homogeneous catalysis (Chapter 7). The transport and kinetic phenomena in both model reactors and industrial reactors are outlined. The section on catalyst preparation (Chapters 8 and 9) is concerned with the preparation of catalyst supports, zeolites, and supported catalysts, with an emphasis on general principles and mechanistic aspects. For the supported catalysts the relation between the preparative method and the surface chemistry of the support is highlighted. The molecular approach is maintained throughout. The first chapter (10) in the section on catalyst characterization summarizes the most common spectroscopic techniques used for the characterisation of heterogeneous catalysts such as XPS, Auger, EXAFS, etc. Temperature programmed techniques, which have found widespread application in heterogeneous catalysis both in catalyst characterization and simulation of pretreatment procedures, are discussed in Chapter 11. A discussion of texture measurement, theory and application, concludes this section (12). The final chapter (13) gives an outline of current trends in catalysis. Two points of view are adopted: the first one focusses on developments in process engineering. Most often these have their origin in demands by society for better processes. The second point of view draws attention to the autonomous developments in catalysis, which is becoming one of the frontier sciences of physics and chemistry. In this book emphasis is on those reactions catalyzed by heterogeneous and homogeneous catalysts of industrial relevance. The integrative treatment of the subject matter involves many disciplines, consequently, the writing of the book has been a multi-author task. The editors have carefully planned and harmonized the contents of the chapters.
Ch. 10. Catalyst Characterization with Spectroscopic Techniques / J.W. Niemantsverdriet -- Ch. 11. Temperature Programmed Reduction and Sulphiding / F. Kapteijn, J.A. Moulijn and A. Tarfaoui -- Ch. 12. The Use of Adsorption Methods for the Assessment of the Surface Area and Pore Size Distribution of Heterogeneous Catalysts / J.J.F. Scholten -- Ch. 13. Future Trends / J.A. Moulijn, P.W.N.M. van Leeuwen and R.A. van Santen.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Elsevier
Keywords: Catalysis; SCIENCE -- Chemistry -- Physical & Theoretical; Catalysis; Katalyse; Katalysatoren; Catalyse -- Congrès.; Catalysis; Electronic books